Association of gender, oral habits, and poor sleep quality with possible sleep bruxism in schoolchildren - Josiane Pezzini SOARES; Angela GIACOMIN; Mariane CARDOSO; Júnia Maria SERRA-NEGRA; Michele BOLAN (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract The aim of this study was to verify the oral habits, symptoms, and characteristics of some children aged 8 to 10 years that could be associated with possible sleep bruxism. A cross-sectional study was performed. Questionnaires were sent to parents to obtain information on sex, age, school shift, sleep quality, parents' perception of children's behavior, and children's oral habits (nail biting, object biting, and lip biting), and symptoms such as headache or earache. In addition, parents reported the frequency of sleep bruxism (no day to 7 days a week). Descriptive analysis and multinomial logistic regression were performed and the level of significance was set at 5%. A total of 1,554 parents of children aged 8 to 10 years participated in this study. Possible sleep bruxism was reported as mild for 65.7%, moderate for 25.3%, and severe for 9% of the children. In the adjusted multinomial logistic regression, boys were 79% more likely to have sleep bruxism (OR: 1.79; 95%CI 1.23-2.60) and were 2.06 more times at risk of being in the habit of lip biting (OR: 2.06; 95%CI 1.26-3.37). Children with possible severe sleep bruxism were 61% more likely to develop object biting (OR: 1.61; 95%CI 1.09-2.39), 52% more likely to have headaches (OR: 1.52; 95%CI 1.01-2.28), and 3.29 more times at risk of poor sleep quality (OR: 3.29; 95%CI 2.25-4.82). Based on the report, boys with lip and object biting habits, headaches, and poor sleep quality presented a higher chance of possible severe sleep bruxism.